NovoLearning: A strategic response to large class problems in teaching non-English department students - Emma Rosana Febriyanti; Raisa Fadilla; Chairil Faif Pasani; Rizky Amelia (UNIB Press, 2022)
Having English for all non-English department students as a compulsory course in the institution is worthwhile for the improvement of students’ ability in using foreign language; however, practically, the students and the lecturers deal with a lot of issues regarding the implementation of the subject itself. Every English class of non-English department is a large class consisting of more than 50 and even 100 students. Handling large classes constitutes a real challenge to every lecturer that it may hinder greater academic achievement and favorable attitudes toward learning. This study aims to find out how NovoLearning program can be the alternative to cope with large class problems of non-English language students. NovoLearning program is an artificial intelligence-based mobile learning that provides a fully integrated training solution, allowing focused English language instruction, communication preparation and integrated skills training. This study employed descriptive qualitative research involving 356 non-English department students from MIPA major namely Mathematics, Biology, Chemistry, Physics, and Natural Science Education Study Programs. Interview, observation, and documentation were employed to obtain the data of this present study. The results show that NovoLearning program can elevate the efficiency of the teaching and learning level to its best quality. It witnessed several views of students that get advantages from the use of the program such as the interactivity, boost on students’ English proficiency, and high-quality feedback. The practical use of this program makes it potential to be applied not only for today’s learning as an alternative to cope with ineffectiveness of large class but also for more advanced learning in the future.